Establishment of Listeria monocytogenes in the Gastrointestinal Tract - Davis, Morgan L. (Microorganisms, 2019)
Listeria monocytogenes is a Gram positive foodborne pathogen that can colonize the gastrointestinal tract of a number of hosts, including humans. These environments contain numerous stressors such as bile, low oxygen and acidic pH, which may impact the level of colonization and persistence of this organism within the GI tract. The ability of L. monocytogenes to establish infections and colonize the gastrointestinal tract is directly related to its ability to overcome these stressors, which is mediated by the efficient expression of several stress response mechanisms during its passage. This review will focus upon how and when this occurs and how this impacts the outcome of foodborne disease.